2020
DOI: 10.3390/pharmaceutics12090798
|View full text |Cite
|
Sign up to set email alerts
|

Lutein-Loaded, Biotin-Decorated Polymeric Nanoparticles Enhance Lutein Uptake in Retinal Cells

Abstract: Age related macular degeneration (AMD) is one of the leading causes of visual loss and is responsible for approximately 9% of global blindness. It is a progressive eye disorder seen in elderly people (>65 years) mainly affecting the macula. Lutein, a carotenoid, is an antioxidant, and has shown neuroprotective properties in the retina. However, lutein has poor bioavailability owing to poor aqueous solubility. Drug delivery to the posterior segment of the eye is challenging due to the blood–retina barrier. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 56 publications
(82 reference statements)
0
13
0
Order By: Relevance
“…After 12 h, 1 mL of 50 mM NH 4 Cl was added to TAC-NMF-FITC and TAC-FITC solution to inactivate unreacted FITC. The final solution of FITC-labelled TAC-NMF and TAC was aliquoted and stored at −20°C until further use, as described in [ 29 , 33 , 34 ]. Figure 2 depicts the FITC conjugation reaction for TAC-NMF-FITC and TAC-FITC formation.…”
Section: Methodsmentioning
confidence: 99%
“…After 12 h, 1 mL of 50 mM NH 4 Cl was added to TAC-NMF-FITC and TAC-FITC solution to inactivate unreacted FITC. The final solution of FITC-labelled TAC-NMF and TAC was aliquoted and stored at −20°C until further use, as described in [ 29 , 33 , 34 ]. Figure 2 depicts the FITC conjugation reaction for TAC-NMF-FITC and TAC-FITC formation.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, compared to free crocetin (589.7 µM), the PLGA crocetin NPs showed a lower IC 50 value (84.7 µM) in inhibiting human breast cancer cell MCF-7 ( Figure 8 B). Also, in a recent study Bolla, et al [ 47 ] used biotin-based PLGA-polyethylene glycol (PEG) for encapsulation of lutein to develop PLGA-PEG-lutein NPs (particle size, <250 nm; ZP, −27.3 mV; EE, 74.6%) and showed a sustained 100% in vitro release after 24 h. Furthermore, they showed a higher lutein intake by retinal pigment epithelial cell ARPE-19 from PLGA-PEG-lutein NPs than from both free lutein and PLGA- lutein NPs ( Figure 8 C), demonstrating that a combination of polymers could possess a greater potential in treating age-related macular degeneration.…”
Section: Preparation Physicochemical Characterization Stability Evaluation and Biological Activitymentioning
confidence: 98%
“…Bioaccessibility is usually determined in vitro by simulating gastric condition with pepsin/HCl (pH 1–2) and intestinal condition with pancreatin/bile salt or trypsin (pH 7–7.5), followed by mimicking an absorption model using Caco-2 cell or dialysis bag [ 42 , 47 , 56 ]. Whereas, the absolute bioavailability in vivo is determined by simultaneous oral administration by gavage and intravenous injection into rats, followed by blood collection and bioactive component analysis at different time intervals and determination of pharmacokinetic parameters including AUC (area under the curve of bioactive component concentration versus time profile), C max (maximum concentration in blood), T max (time to reach maximum concentration in blood) and t 1/2 (time to reach half the maximum concentration) [ 44 ].…”
Section: In Vitro Release Gastrointestinal Absorption and Bioaccessibility/bioavailabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The anticancer properties of biotinylated nanosystems have received great attention from researchers ( Table 4 ) [ 118 ]. The era of biotinylated DDS has been started from the article published in 2004 by Russell-Jones et al It has been reported that the therapy of colon cancer (using Colo-26 xenograft model) with the biotin-labelled doxorubicin-hydroxypropylmethacrylic acid (Dox-HMPA) complex provides enhanced efficiency when compared to the control group.…”
Section: Biotin—targeted Nanoparticlesmentioning
confidence: 99%